2018
DOI: 10.1093/advances/nmx002
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Attention Deficit Hyperactivity Disorder: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: An association between vitamin D and attention deficit hyperactivity disorder (ADHD) has been proposed by several researchers in recent years; however, the investigations have led to inconsistent results. The present study was conducted to summarize the published observational data on the relation between vitamin D status and the likelihood of ADHD. Online databases, including PubMed, the ISI Web of Science, Google Scholar, and Scopus, were checked up to June 2017 for relevant observational studies. A random-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 56 publications
1
44
1
2
Order By: Relevance
“…14 Additionally, vitamin D deficiency is linked to psychiatric conditions including ADHD, autism, depression, and schizophrenia. [15][16][17][18] These clinical findings warrant further study. Based on our previous findings, we hypothesized that vitamin D insufficiency or deficiency may be contributive to the increased susceptibility of CTDs, and therefore vitamin D3 supplementation will reduce the severity of tic symptoms in children with CTDs.…”
Section: Introductionmentioning
confidence: 80%
“…14 Additionally, vitamin D deficiency is linked to psychiatric conditions including ADHD, autism, depression, and schizophrenia. [15][16][17][18] These clinical findings warrant further study. Based on our previous findings, we hypothesized that vitamin D insufficiency or deficiency may be contributive to the increased susceptibility of CTDs, and therefore vitamin D3 supplementation will reduce the severity of tic symptoms in children with CTDs.…”
Section: Introductionmentioning
confidence: 80%
“…They found a high prevalence of VD deficiency in ADHD (>90%), which was significantly higher than that of HCs. Recently, Khoshbakht et al (9) undertook a meta-analysis on VD levels and ADHD. They discovered that reduced VD levels were correlated significantly with the likelihood of ADHD, and that perinatal suboptimal VD concentrations were correlated significantly with a higher risk of ADHD in later life.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that low maternal levels of VD during pregnancy can lead to an increased risk of offspring with ADHD (7,8). Studies have shown that children suffering from ADHD have a reduced serum concentration of 25-hydroxyvitamin D (25(OH)D) as compared with that in healthy children (9)(10)(11). VD supplementation is an adjunct therapy used to overcome symptoms of ADHD and has comparatively few side effects (12).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, prospective studies show that low perinatal vitamin D concentrations increase risk of diagnosis later in life (RR: 1.40; 95% CI = 1.09–1.81). This meta-analysis must be interpreted with caution, as removal of one study abolishes the correlation [ 88 ]. Considering the risk of ASD and ADHD observed with vitamin D deficiency, vitamin D may join folate as recommended supplementation in women preparing for pregnancy.…”
Section: Vitamin D/vitamin D Receptor Signalling In Neurodevelopmentamentioning
confidence: 99%